An Example from Provincial Alevi Literature: A Manuscript from the Çorum Branch of Şah İbrahim Veli Ocağı - Erol, Ufuk (Journal of Alevism-Bektashism Studies, 2023)
Studies on the history of religion and Sufism in the Ottoman Empire have thus far focused on prominent scholarly and political centers of the empire such as İstanbul, Bursa, Cairo and Damascus. Compared to the written literature produced in these centers, that of Sufi groups in provinces has been less studied. In the last 20 years scholars started to study the Alevi tradition and its literature that were always dismissed in city centers in the Ottoman Empire. The fact that Alevi manuscripts have remained in the hands of Alevi families rather than at public libraries is also an important reason why Alevi tradition and literature have been less studied. The manuscript which is analyzed in this article was donated to Hacı Bektâş-ı Veli Research Center from the Perspective of Turkish Culture at Hacı Bayram Veli University by Arap Ali Gazioğlu, an Alevi religious master (dede) from the Çorum branch of Şah İbrahim Veli Ocağı (the hearth of Şah İbrahim Veli), and it is catalogued under the number B375 in the archive of the center. The topics in the manuscript consist of four gates and forty stations, religious issues, and various religious stories, out of which the first two topics are analyzed in this article. The four gates and forty stations doctrine on which Alevi and Bektashi beliefs are based is analyzed in the manuscript with an exegesis of certain Quranic verses. Religious and social problems that Alevis may face in their daily lives and the answers for these problems are also explained under the title of müşküller (difficult/problematic conditions). Considering the content of the manuscript and the exegesis of certain Quranic verses, we can conclude that Alevis and particularly those belonging to Şah İbrahim Veli Ocağı in the province of Çorum had a developed written religious corpus. It can be argued that Alevis have interpreted the Quran from an esoteric/inner-worldy perspective when expounding their Sufi path. The content of the manuscript shows us that Alevism has not only an oral culture but also a rich written culture, both of which support each other.
Keywords: Alevism; oral culture; written culture; Quran; manuscript; Şah İbrahim Veli Ocağı